Design, implementation and assessment of complex engineering problems for the undergraduate engineering programme - Rasheduzzaman, Mirza; Doulah, A. B. M. S. U.; Hossain, M. Mofazzal (Journal of Turkish Science Education, 2026)
In the era of the Industrial Revolution 4.0, Outcome-Based Education (OBE) has been adopted worldwide to meet the growing demand for engineering graduates with the knowledge, skills, and attitudes to solve complex engineering problems. In this work, a methodology is presented for designing, implementing, and assessing students’ performance in a Complex Engineering Problem group project, in accordance with the guidelines of the Board of Accreditation for Engineering and Technical Education (BAETE) in Bangladesh. The mapping of course outcomes (COs) to programme outcomes (POs), the knowledge profile, attributes of complex engineering problem-solving, and complex engineering activities is presented. The design and implementation of an effective assessment key to measure students’ performance is presented using a case study in the Microprocessor and Embedded System course in the Electrical and Electronic Engineering programme. This contribution will be very useful to the teaching community in developing the OBE curriculum as well as researchers in the field of engineering and technical education.
Keywords: Complex engineering problem solving; complex engineering activities; outcome-based education; assessment rubric; accreditation